Comparative transcriptome combined with morpho‐physiological analyses revealed key factors for differential cadmium accumulation in two contrasting sweet sorghum genotypes. Issue 2 (3rd August 2017) - Feng, Juanjuan; Jia, Weitao; Lv, Sulian; Bao, Hexigeduleng; Miao, Fangfang; Zhang, Xuan; Wang, Jinhui; Li, Jihong; Li, Dongsheng; Zhu, Cheng; Li, Shizhong; Li, Yinxin
Summary: Cadmium (Cd) is a widespread soil contaminant threatening human health. As an ideal energy plant, sweet sorghum ( Sorghum bicolor (L.) Moench) has great potential in phytoremediation of Cd‐polluted soils, although the molecular mechanisms are largely unknown. In this study, key factors responsible for differential Cd accumulation between two contrasting sweet sorghum genotypes (high‐Cd accumulation one H18, and low‐Cd accumulation one L69) were investigated. H18 exhibited a much higher ability of Cd uptake and translocation than L69. Furthermore, Cd uptake through symplasmic pathway and Cd concentrations in xylem sap were both higher in H18 than those in L69. Root anatomy observation found the endodermal apoplasmic barriers were much stronger in L69, which may restrict the Cd loading into xylem. The molecular mechanisms underlying these morpho‐physiological traits were further dissected by comparative transcriptome analysis. Many genes involved in cell wall modification and heavy metal transport were found to be Cd‐responsive DEGs and/or DEGs between these two genotypes. KEGG pathway analysis found phenylpropanoid biosynthesis pathway was over‐represented, indicating this pathway may play important roles in differential Cd accumulation between two genotypes. Based on these results, a schematic representation of main processes involved in differential Cd uptake and translocation in H18 and L69 is proposed, which suggests that higher Cd accumulation in H18 depends on a multilevel coordination of efficient Cd uptake and transport, including efficient root uptake and xylem loading, less root cell wall binding, and weaker endodermal apoplasmic barriers.